Nonlinear adaptive controller of mechanical transmission systems with backlash - Nguyen, Duy Anh; Tran , Ngoc Cong Thuong (Journal of Technical Education Science, 2017)
Backlash appears in most of mechanical transmission systems and is one of nonlinearity characteristics leading to the error in position and velocity control. To control a mechanical system with backlash, the system parameters such as: damping, spring stiffness, mass, backlash gap have to be identified exactly. However, it is difficult to measure these parameters in real system because of low measurement accuracy or cost. This paper proposes a new method to compensate backlash by using Model Reference Adaptive Control (MRAC) and a nonlinear compensator without pre-determined backlash parameters. The adaptive controller assures the controllability of the different systems with uncertain parameters. While, the nonlinear compensator is used to overcome the effect of backlash. Based on the results of Gang Tao, the mathematical function of backlash and backlash inverse are presented. After that, the mass-spring-damping model is applied to approximate mathematical transmission systems. Nonlinear adaptive controller is designed and simulated. The simulation results show that errors because of backlash are reduced and the controller tracks the desired input properly.